1996
DOI: 10.1159/000127136
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Histaminergic and Serotonergic Neurons in the Hypothalamic Regulation of Prolactin and ACTH Secretion

Abstract: Serotonergic and histaminergic neuronal systems are both involved in mediation of the stress-induced release of the pituitary hormones prolactin (PRL) and ACTH. We investigated the possibility of an interaction between serotonin (5-HT) and histamine (HA) in regulation of PRL and ACTH secretion in conscious male rats. Animals were pretreated systemically with antagonists to 5-HT1, 5-HT2 or 5-HT3 receptors prior to intracerebroventricular (icv) administration of HA. The 5-HT1+2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
(11 reference statements)
3
10
0
1
Order By: Relevance
“…This indicates that the posterior hypothalamus is involved in the mediation of the serotonergic stimulation of PRL secretion whereas an intact posterior hypothalamus is not required for induction of an ACTH and β-END response to serotonergic neuronal activation. The present results are similar to our finding that inhibition of neuronal HA synthesis or release or blockade of postsynaptic H 1 or H 2 receptors decreased the PRL response but not the ACTH response to serotonergic neuronal activation induced by 5-HTP and fluoxetine [37], present study] further suggesting that the effect of posterior hypothalamic lesion was due to destruction of histaminergic neurons. Furthermore, the preservation of the ACTH and β-END responses to serotonergic neuronal activation in lesioned animals indicates that the serotonergic neuronal system was not destroyed by the lesion, eliminating the possibility that the reduced hormone responses in the animals exposed to stress or LPS was due to damage of serotonergic nerve fibers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that the posterior hypothalamus is involved in the mediation of the serotonergic stimulation of PRL secretion whereas an intact posterior hypothalamus is not required for induction of an ACTH and β-END response to serotonergic neuronal activation. The present results are similar to our finding that inhibition of neuronal HA synthesis or release or blockade of postsynaptic H 1 or H 2 receptors decreased the PRL response but not the ACTH response to serotonergic neuronal activation induced by 5-HTP and fluoxetine [37], present study] further suggesting that the effect of posterior hypothalamic lesion was due to destruction of histaminergic neurons. Furthermore, the preservation of the ACTH and β-END responses to serotonergic neuronal activation in lesioned animals indicates that the serotonergic neuronal system was not destroyed by the lesion, eliminating the possibility that the reduced hormone responses in the animals exposed to stress or LPS was due to damage of serotonergic nerve fibers.…”
Section: Discussionsupporting
confidence: 93%
“…serotonergic, dopaminergic, catecholaminergic) neurons in the brain, whereby they mediate inhibition of the release of HA or other amines [23, 24, 34, 35, 36]. However, we have recently found that the H 3 receptor agonists do not participate in the hormone response to serotonergic neuronal activation [37]. The present results suggest that the inhibitory effect of H 3 receptor activation is caused via an action on presynaptic receptors located on histaminergic neurons rather than on other aminergic neurons, since their effect of the H 3 receptor agonists was similar to that induced by suppression of neuronal HA synthesis by α-FMH and blockade of postsynaptic H 1 or H 2 receptors [17, 18, 19, 20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…However, in other studies, HA did not affect the turnover of dopamine in the median eminence [17, 18]. Other studies have indicated that the effect of HA is mediated via an interaction with vasopressinergic as well as serotonergic neurons [14, 19, 20, 21]. …”
Section: Introductionmentioning
confidence: 86%
“…In addition, we have recently found that HA interacts with prostaglandins but not with serotonin (5-HT) in the regulation of the hypothalamic-pituitary-adrenal (HPA) axis [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…The effect of HA on ACTH secretion is caused by an effect on corticotropinreleasing hormone neurons and vasopressin (AVP) neurons in the paraventricular nucleus (7-9) -probably via an interaction with prostaglandins (10). The effect of HA on PRL secretion seems to involve AVP and serotonin (11,12), while the involvement of dopamine is in question (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%